Conceptual Perspectives on State Fragility - D. P. Elagin (Vestnik MGIMO-Universiteta)
The article explores scientific discourse on the phenomenon of state fragility and reviews contemporary research that aims to uncover what factors account for the emergence of states that are vulnerable to risks and crises and lack the capacity to deliver a response on their own. In order to achieve this goal, the author analyzes the evolution of the state fragility concept and reviews the literature on its causes. The article finds significant advancement in scientific thought about fragile states, acknowledg ing their continuous and multi-dimensional nature (the 'ALC' and 'OECD' approaches). However, these approaches tend to view fragile states as a deviation from the Europe an nation-state model and focus more on the attributes of fragility (inability to perform core functions of the state or lacking the capacity to cope with risks and crises) while failing to produce a precise explanation for its causes. Hence, there is a need to analyze the process of fragile states formation and its consequences, i.e., to look at the macrohistorical dimension of state fragility. A better understanding of the historical context of state fragility and stricter identification criteria for the subgroup of severely and chronically fragile states allows identifying some structural explanatory factors such as rigidity of pre-independence colonial state borders, heterogeneity of population, and preferences that constraints collective action and small economic size. The literature review presented in the article finds that fragile states often have an insufficient tax base to guarantee the efficient provision of public goods. There are also agency factors that contribute to increased state fragility. This review also finds that imperfect political institutions may produce kleptocratic political regimes detached from the population's interests and irresponsive to them. Consequently, they are likely to deny or limit access to public goods for some population groups. A combination of these factors is likely to create weak and fragile states, with the extent of fragility being context-specific. Recognizing the impact of the factors discussed in the article may help produce better policy responses to various development problems that plague fragile states.